Evaluation of concentrated growth factor as an adjuvant on crestal bone levels around dental implants - Sitamahlakshmi, K.; Jampani, Narendra Dev; Songa, Vajra Madhuri; Lahari, Buggapati; Kumar, Govardhani Krishna (International Journal of Research in Medical Sciences, 2022)
Background: Dental implants have a long-term success rate when the osteointegration is maintained with minimal crestal bone loss yearly. The present study evaluates the crestal bone loss around Osseointegrated implants using a concentrated growth factor as an added factor to preserve the crestal bone levels. Methods: Total of 20 patients with a single edentulous site were included in the study and divided into test and control groups. Test group concentrated growth factor is placed along with implant, and the control group implant placed without concentrated growth factor. Soft tissue parameters like modified sulcus bleeding index (mSBI) and modified plaque index (mPI) were done three and nine-month after implant placement. Hard tissue parameters like crestal bone levels (CBL), bone density, and volume were done immediately after implant placement and nine-month of implant placement using cone-beam computed tomography (CBCT). Results: Intragroup comparison from baseline to nine-month in the test group showed a significant difference at nine months at different points compared to the control group in hard and soft tissue parameters. On intergroup comparison was statically insignificant. Conclusions: Concentrated growth factor aids in enhancing bone density and faster healing around dental implants, so it can be used as an advancement in personalized medicine and promoting osseous regeneration by increasing the density and volume of bone around the dental implants.